THE IMPACT OF SAAC METHOD ON READING COMPREHENSION AND INTEREST OF EIGHTH GRADE STUDENTS AT SMPN 4 RAMBUTAN - Yohana Aloy; Masagus Firdaus; Mulyadi Mulyadi (Universitas Wiralodra, 2025)
The study aimed to explore how the SAAC (State, Assign, Action, Complete) method enhances reading comprehension and interest among eighth-grade students at SMPN 4 Rambutan. Conducted using Classroom Action Research (CAR) based on Kemmis and Taggart’s model, the study involved class 8.1, consisting of 32 students (14 males and 18 females), and was carried out in two cycles. In cycle 1, 20 students (62.5%) met the minimum passing criteria (≥73), but observations indicated that student participation was still at a fair level, and the teacher had not fully encouraged engagement. In cycle 2, 28 students (87.5%) met the criteria, showing improved participation and interest, while the teacher also enhanced her ability to engage students more effectively. To boot, results from the reading interest questionnaire revealed an increase from an initial score of 2.86 to 3.50, indicating a higher enthusiasm for reading. These findings confirm that the SAAC method effectively improves students’ reading comprehension and interest at SMPN 4 Rambutan. This study was conducted with a single class over a short period of time. Therefore, future studies should include larger, more diverse samples to better evaluate the sustained impact of the SAAC method on reading comprehension and interest.